Innovation on Demand: Can Public Procurement Drive Market Success of Innovations - Birgit Aschhoff; Wolfgang Sofka (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Public procurement has been at the centre of recent discussions on innovation policy on both European and national levels (e.g., Aho-Report, Barcelona Strategy). It has a large potential to stimulate innovation since it accounts for 16% of combined EU-15 GDP. We embed public procurement for innovation into the broader framework of public policies to stimulate innovation: regulations, R&D subsidies and knowledge infrastructure (i.e. basic research at universities). We synthesize the characteristics of all four instruments based on existing literature and quantitatively compare their effects on innovation success. Our empirical investigation rests upon a survey of more than 1,100 innovative firms in Germany. Our survey puts us in the position to trace all sources of valuable innovation impulses, namely public customers, law and regulations, universities and public funding for R&D. We relate these sources back to innovation success. We find that (non-defense related) public procurement and knowledge spillovers from universities propel innovation success equally. In a second step, we explore whether these effects vary across firms (e.g. size, location, industry). The benefits of university knowledge apply uniformly to all firms. However, public procurement is especially effective for smaller firms in regions under economic stress as well as in distributive and technological services. Based on these findings targeted policy recommendations can be developed.
Keywords: C34; H32; O38; 330; Innovation policy; public procurement; comparison of instruments; innovation success; Innovationspolitik; Öffentliche Beschaffung; Forschungskooperation; Wirtschaftspolitische Wirkungsanalyse; Innovation; Erfolgsfaktor; Deutschland